Characterisation of handling and service surface damage on Nickel alloys caused by low velocity impacts of blunt hard objects. (April 2017) - Fleury, R.M.N.; Nowell, D.; Sui, T.; Ying, S.; Korsunsky, A.M.; Tai, Y.H.; Silva, F.
Highlights: Geometrical characterisation of dent damage caused by low velocity impact of hard blunt object on Nickel superalloys at different impact velocities. Validation of a finite element model to predict the dent geometry and residual stresses by comparison with the experimental results. Residual stress measurement by laboratory sourced X-ray diffraction on dented specimens. Comparison between residual stresses measured experimentally with the residual stresses predicted by the finite element model. Abstract: This paper presents a characterisation of surface damage, more specifically dents, caused by low velocity impacts of blunt objects on RR1000 Nickel superalloys. These are representative of damage that may occur during handling and service of components during manufacturing or maintenance. The characterisation of dents produced in laboratory tests is carried out both in terms of their geometry and the residual stresses the damage. A finite element model is presented and the results are validated in terms of dent geometry produced for different impact velocities. The stress distribution predicted by the numerical model is also compared with experimentally measured stresses via X-ray diffraction for validation of the model. The residual stresses obtained from the finite element (FE) model and their implications to fatigue and crack propagation lives are also discussed here.